Platform - Jia Zhang Ke; Yu Lik Wai; Wang Hong-wei; Zhao Tao; Liang Jing Dong (Artificial Eye, 2012)
Jia Zhang Ke’s film follows a small group of friends from adolescence to adulthood. The friends live in the small town of Fenyang in a remote province of China. Life is difficult enough for young people in a remote country town, but even more so for the four main characters, who have artistic leanings, but living under a strict Maoist regime their personalities are suppressed by strict parents and idealogically-sound instructors and leaders. They are only able to express their talent in a Cultural Team, a troupe of performers who travel from village to village performing propaganda songs and routines. The years bring sweeping changes, including the privatisation of the troupe, who are bought-out by their chief and turn into the All-Star Rock and Breakdance Band, but their dreams and expectations, exemplified in the Chinese pop-song 'Platform', end up turning to dust. [film.thedigitalfix.com]
Keywords: DVD-Video